2016
DOI: 10.1002/btpr.2269
|View full text |Cite
|
Sign up to set email alerts
|

Elastin‐like‐polypeptide based fusion proteins for osteogenic factor delivery in bone healing

Abstract: Modern treatments of bone injuries and diseases are becoming increasingly dependent on the usage of growth factors to stimulate bone growth. Bone morphogenetic protein-2 (BMP-2), a potent osteogenic inductive protein, exhibits promising results in treatment models, but recently has had its practical efficacy questioned due to the lack of local retention, ectopic bone formation, and potentially lethal inflammation. Where a new delivery technique of the BMP-2 is necessary, here we demonstrate the viability of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The binding of the LDLR3-ELP to the lentiviral vector indicates that the binding ability of LDLR3, in the fusion protein LDLR3-ELP, remained unaffected. This observation is similar to previous studies by several others and us for chimeric ELP fusion proteins where the biological activity of the functional domain remains unaffected by the ELP fusion ( 31 , 32 ). Moreover, the inhibitory activity of LDLR3-ELP without KGF-ELP also demonstrates that its potential application as an agent in antiviral therapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The binding of the LDLR3-ELP to the lentiviral vector indicates that the binding ability of LDLR3, in the fusion protein LDLR3-ELP, remained unaffected. This observation is similar to previous studies by several others and us for chimeric ELP fusion proteins where the biological activity of the functional domain remains unaffected by the ELP fusion ( 31 , 32 ). Moreover, the inhibitory activity of LDLR3-ELP without KGF-ELP also demonstrates that its potential application as an agent in antiviral therapy.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that the fusion protein, LDLR3-ELP, maintained the phase transition property and self-assembled into nanoparticles above transition temperature. These fusion proteins retained the biological activity and phase transitioning properties of ELPs, as shown in previous studies ( 29 , 31 , 32 ). This allowed recombinant expression and simple purification of the fusion proteins by a series of hot and cold cycles.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When compared with the control, BMP-V40C2 showed higher alkaline phosphatase activity, higher mRNA levels of osteoblast-specific transcription factor Osterix (OSX) and higher calcium deposition after a 21-day treatment. As such, this study demonstrated that the fusion protein not altered the osteogenic ability of BMP-2 and that the construct retained the transition ability of ELRs [114].…”
Section: Skeletal System Regenerationmentioning
confidence: 58%
“…Some research has been devoted to designing ELRs capable of forming nanoparticles that present growth factors on their surfaces and that can interact with cells. These include growth factors for chronic skin wound treatment [50], for the induction of bone regeneration [51] or the treatment of neuronal injuries [52]. Stromal cell-derived growth factor-1 (SDF1) is a small cytokine belonging to the chemokine family that promotes neovascularization and has been proven to provoke a faster re-epithelialization of skin wounds.…”
Section: Nanoparticles From Hybrid Elrsmentioning
confidence: 99%